I only see the polynomial
, so I'll factor that one.
We can use two approaches: the most "standard" one requires us to find the roots of the polynomial. Then, for each root
we write the factor
, and decompose the polynomials like this:
![x^2-36=0 \iff x^2 = 36 \iff x = \pm√(36) = \pm 6](https://img.qammunity.org/2019/formulas/mathematics/high-school/oyeee742idpiulvfxsxol65hlwnqd31rd8.png)
So, the root
yields the factor
, and the root
yields the factor
. This means that the polynomial can be factored as
![x^2-36 = (x+6)(x-6)](https://img.qammunity.org/2019/formulas/mathematics/high-school/gjbwemschw99eg5s3u41n126fpknb4r4qu.png)
Alternatively, you can observe that the polynomial comes in the form
, and it can be factored as
![a^2-b^2 = (a-b)(a+b)](https://img.qammunity.org/2019/formulas/mathematics/high-school/lfc34n5c4orwkhiwkn6lghfacx1y5wkriu.png)
which again leads to
![x^2-36 = (x)^2 - (6)^2 = (x+6)(x-6)](https://img.qammunity.org/2019/formulas/mathematics/high-school/zmcqrxan7ewq0rgikkv7c78u7cxvxa2g76.png)